Hes repressors are essential regulators of hematopoietic stem cell development downstream of Notch signaling - Guiu, Jordi (The Rockefeller University Press, 2013)
Previous studies have identified Notch as a key regulator of hematopoietic stem cell (HSC) development, but the underlying downstream mechanisms remain unknown. The Notch target Hes1 is widely expressed in the aortic endothelium and hematopoietic clusters, though Hes1-deficient mice show no overt hematopoietic abnormalities. We now demonstrate that Hes is required for the development of HSC in the mouse embryo, a function previously undetected as the result of functional compensation by de novo expression of Hes5 in the aorta/gonad/mesonephros (AGM) region of Hes1 mutants. Analysis of embryos deficient for Hes1 and Hes5 reveals an intact arterial program with overproduction of nonfunctional hematopoietic precursors and total absence of HSC activity. These alterations were associated with increased expression of the hematopoietic regulators Runx1, c-myb, and the previously identified Notch target Gata2. By analyzing the Gata2 locus, we have identified functional RBPJ-binding sites, which mutation results in loss of Gata2 reporter expression in transgenic embryos, and functional Hes-binding sites, which mutation leads to specific Gata2 up-regulation in the hematopoietic precursors. Together, our findings show that Notch activation in the AGM triggers Gata2 and Hes1 transcription, and next HES-1 protein represses Gata2, creating an incoherent feed-forward loop required to restrict Gata2 expression in the emerging HSCs.